Acute ST elevation myocardial infarction (STEMI) in Young Male with Nephrotic Syndrome: A case report - Ratna Pancasari; Cholid Tri Tjahjono; Anna Fuji Rahimah; Indra Prasetya (Heart Science Journal, 2021)
Background: In young males, an acute myocardial infarction is an uncommon event. Thrombolism caused by nephrotic syndrome (NS) is one of the pathophysiologies of their infarctions.Case Illustration: A-24-y.o male patient, presenting with prolong typical chest pain since 72 hours before admission. The chest leads on an electrocardiogram (ECG) indicated ST-Elevation. Cardiac troponin was significantly raised. Since the previous two weeks, he has been experiencing nephrotic syndrome symptoms including anasarca edema.It was supported by laboratory data which is obtained proteinuria, hyperlipidemia and hypoalbuminemia. A complete acute occlusion of the proximal portion of the left anterior descending artery was revealed by coronary angiography. Increased fibrinogen levels appeared to be a contributing factor for hypercoagulable state in this patient, implying a correlation between coronary thrombosis and nephrotic syndrome.Discussion: Myocardial infarction (MI) is rare in young males, but it occurs 8 times more often in patients with NS than in the general population. Clinicians should pay closer attention to the history of previous diseases with a high risk of thromboembolism in young patients with MI, and they should specifically promote thromboembolism prevention and care in patients with renal disease to decrease the incidence of thromboembolism complications.Conclusion: Nephrotic syndrome should be considered as a contributing factor in any patient presenting with acute STEMI, particularly in young males.